Upaya Polri dalam Melakukan Penegakan Hukum Terhadap Kelompok Kriminal Bersenjata di Wilayah Papua Tengah - Khozin, Muhammad Noor; Sari, Nia Ayu Mayang (PT Elaborium Elevasi Indonesia, 2025)
The Armed Criminal Group (KKB) in Papua is a separatist movement that has political objectives to separate itself from the territory of the Unitary State of the Republic of Indonesia or to liberate Papua. This separatist movement includes violence, kidnapping and human rights violations, and murder. Based on its history, this separatist movement has been going on for a long time since 1965 under the name of the Free Papua Organization (OPM). Both have caused unrest for the Papuan people and left the roots of the problem unsolved. Because of this, this research aims to find out how the Police's efforts in enforcing the law against the KKB and to find out the Criminal Code Articles that can be enforced in law enforcement efforts against KKB. The method used in this research is normative juridical research with a statutory approach. The results of this study explain that the Police have a very crucial role in handling the KKB conflict. This is in line with its function as a law enforcer in realizing public security and order. In handling the provocation group, the Police approached the Papuan people and jointly opened a space for dialog in order to eradicate the root of the problem.